Long radiative lifetimes of excitons in monolayer transition-metal dichalcogenides MX2 (M = Mo, W; X = S, Se). (13th December 2017) - Mohamed, Nur Baizura; Lim, Hong En; Wang, Feijiu; Koirala, Sandhaya; Mouri, Shinichiro; Shinokita, Keisuke; Miyauchi, Yuhei; Matsuda, Kazunari
Abstract: We studied the effective exciton radiative lifetimes of monolayer two-dimensional transition-metal dichalcogenides MX 2 ( M = Mo, W; X = S, Se). The photoluminescence (PL) quantum yield and PL decay time were measured for monolayer MoS2, MoSe2, WS2, and WSe2 at room temperature. Effective exciton radiative lifetimes of >10 ns were determined from the PL quantum yield of 10 −2 to 10 −3 and the PL decay time of several hundred picoseconds. The results are explained on the basis of the long radiative lifetime of bright excitons at a low temperature limit, a finite exciton coherence area of several square nanometers, and the population of dark exciton states.